Applying sports science to optimize health and performance in figure skating (10th Annual Congress of the US Figure Skating Sports Medicine Society, 2005)
Konferenzband der 10. Jahreskonferenz der Amerikanischen Gesellschaft für Medizin im Eiskunstlauf mit Zusammenfassungen zu folgenden Themen: - New technology and research of sustom orthotics - The need for Training Notebooks: Developing a Mental Training Program - Tam physician pre-competition phone call can be a valuable preventive strategy in identifying and treating medical issues in world team athletes - A summary of injuries and a model for medical care during national synchronzied team skating competition - Analyzing Technique of Figure Skaters using the Dartfish Program: Access to this program can bring scientific information to coaches and skaters and aid in the development of a skater`s performance. - Best Adult Interaction Styles for Enabling Teen Athlete Performance - A Readiness Pyramid for Achieving Peak Performance - Pilates training for skaters in conjunction with psychological skills training - Brachial artery transection in a synchronized teamskater - Adult skating: The possibilities are endless!